Bipolar Coagulation Aneurysm Dome Remodeling (Aneurysmorrhaphy) for Middle Cerebral Artery Aneurysms - Kulwin, Charles (Cureus, 2020)
Adequate visualization of the proximal and distal vessels and clip reconstruction of the bifurcation with complete aneurysm neck exclusion are often difficult in the setting of bulbous small- and moderate-sized middle cerebral artery (MCA) aneurysms. We describe our experience with bipolar aneurysm dome remodeling in the setting of bulbous MCA aneurysms. The charts of the senior author’s (Aaron Cohen-Gadol) patients who underwent clip ligation of their MCA aneurysm (220 patients), and more specifically those whose aneurysm clipping was facilitated through bipolar coagulation remodeling (8 patients), were reviewed. Patient demographics, aneurysm characteristics, and postoperative angiographic results were analyzed. Eight patients with eight MCA aneurysms were treated through this technique over a six-year period. Their mean age was 53 years, and six of the eight patients were women. Two involved the anterior temporal artery, and the rest were at the M1 bifurcation or trifurcation. Three of the eight were ruptured; the mean aneurysm maximum diameter was 7 mm. Postoperative angiography demonstrated complete aneurysm obliteration in seven of eight patients; one patient had an asymptomatic mild stenosis of her anterior temporal artery’s origin, and another had a small neck remnant in the setting of a highly atherosclerotic neck. On the basis of this experience, dome coagulation remodeling of small- and moderate-sized bulbous aneurysms in the setting of poor proximal and distal vessel visualization was found to be safe for facilitating aneurysm clipping and offers more desirable clip deployment.